Theoretical analysis of a diffusion flame established in an inert porous medium - Max Akira Endo Kokubun (2014)
In this work we analyze a steady, planar diffusion flame established in an inert porous matrix. Thc geomotry under consideration is a stagnation-point flow against a condensed (liquid) phase, with all the system (gas and liquid) immersed in an inert porous matrix. In order to better understand the coupled physical processes that occur in this confined problem, we divide the present work in three distinct, but closely related, parts. In the first part we analyze the frozen impinging flow against a hot, impermeable wall (the gas is confined in an inert porou matrix). This configuration allow us to study the heat transfer problem occurring inside the porous rnatrix. In the second part we replace the impermeable wall by a pool of liquid and analyze tho steady vaporization regime that is established when tho impinging flow is at a higher temperature than the liquid boiling temperature. In this case, the heat and rnass transfer confined problem is analyzed. Then, in the third part we consider the impinging jet to be oxidant and the liquid to be fuel. By considering that the conditions are such that a diffusion flame is established, we analyze the influence of the porous matrix in the overall flame properties. Finally, in the Appendix we perforrn an asyrnptotic analysis of the extinction of a diffusion flame established in an inert porous chamber. This analysis is made in order to shed some light on how the gas-solid heat cxchange modifies the extinction limits of such confined flames.